The Relationship Between Service Quality, Facilities, And Effective Communication With Patient Satisfaction At Carolus Serpong Hospital In 2025 - Siska Ayu Puspita (CV. AFDIFAL MAJU BERKAH, 2026)
Patient satisfaction is a crucial indicator of hospital service quality amidst increasing public demand for better healthcare. This study aims to analyze the relationship between service quality, facilities, and effective communication on outpatient satisfaction in the pediatric and obstetrics clinics of Carolus Hospital Serpong in 2025. Using an analytical quantitative cross-sectional design with purposive sampling of 100 respondents, data were collected through a valid (r>0.361) and reliable (α=0.978) SERVQUAL questionnaire, analyzed with Chi-Square and SPSS. The results showed that 80% of respondents were satisfied, with good service quality (61%), facilities (65%), and effective communication (75%). There was a significant relationship between service quality (p=0.016; OR=3.857), facilities (p=0.04; OR=6.896), and effective communication (p=0.009; OR=4.33) on patient satisfaction, with facilities having the strongest influence. It was concluded that the three variables were significantly related to patient satisfaction, and it was recommended that parking facilities and nurse communication training be improved.